The Application of Coorperative Script in Economics Lesson to Improve Learning Outcomes - Yohana Ose Bele; Muhammad Shahrun; Maria Ermelinda Lering; Nhelbourne Mohammad (Jurnal Praktik Baik Pembelajaran Sekolah dan Pesantren, 2023)
This study aims to improve learning outcomes in economics subjects by applying the cooperative script method. This type of research applies class actions with two cycles. The subjects of the study were 10th grade learners who took economics lessons on the topic of consumer and producer behavior. Learning outcomes are measured using multiple choice tests.  After two cycles, learners increased their learning outcomes from an average of 77.14 to 79.04. The percentage of students who met learning completion increased from 80.95% to 100%. These results explain that the cooperative script method has the potential to improve learning outcomes. An aspect that is thought to be a success factor is the convenience of learning with group work.